Pengaruh Gaya Kepemimpinan Direktif, Lingkungan Kerja, dan Budaya Organisasi Kerja terhadap Kinerja Karyawan Perum Bulog Kantor Wilayah Lampung - Rama Putra Jambak; Defia Riski Anggarini (Universitas Sam Ratulangi, 2024)
This research aims to determine the directive leadership style, work environment, and organizational culture on the performance of Perum Bulog employees at the Lampung Regional Office. The method used in this research is quantitative. The sampling technique chosen was saturated sampling. This was done because the population was relatively small. In this research, the samples taken were all 49 employees of Perum BULOG in the city of Bandar Lampung. The data collection technique used was a questionnaire via Google Forms. The data analysis technique used is multiple linear regression analysis. The research results show that: (1) leadership style has a positive and significant effect on employee performance; (2) the environment has a positive and significant influence on employee performance; (3) organizational culture has a positive and significant effect on employee performance; and (4) directive leadership style, work environment, and organizational culture together influence the performance of Perum Bulog employees at the Lampung Regional Office.